2013
DOI: 10.1155/2013/648431
|View full text |Cite
|
Sign up to set email alerts
|

Driver Sleepiness Detection System Based on Eye Movements Variables

Abstract: Driver sleepiness is a hazard state, which can easily lead to traffic accidents. To detect driver sleepiness in real time, a novel driver sleepiness detection system using support vector machine (SVM) based on eye movements is proposed. Eye movements data are collected using SmartEye system in a driving simulator experiment. Characteristic parameters, which include blinking frequency, gaze direction, fixation time, and PERCLOS, are extracted based on the data using a statistical method. 13 sleepiness detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Ahlstrom et al (2013) used AttenD to study the driver distraction, on a database of seven drivers. Smart eyes has also been used by Jin et al (2013), in a simulator to extract blink frequency, gaze direction, fix time and the PERCLOS, then these features are used by Support Vector Machine (SVM) to detect sleepiness among twelve drivers. Miyaji and Kawanaka (2010) have used Adaboost and SVM to classify bio-signals and facial expression data coming from ECG and the eye tracking system FaceLAB.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahlstrom et al (2013) used AttenD to study the driver distraction, on a database of seven drivers. Smart eyes has also been used by Jin et al (2013), in a simulator to extract blink frequency, gaze direction, fix time and the PERCLOS, then these features are used by Support Vector Machine (SVM) to detect sleepiness among twelve drivers. Miyaji and Kawanaka (2010) have used Adaboost and SVM to classify bio-signals and facial expression data coming from ECG and the eye tracking system FaceLAB.…”
Section: Related Workmentioning
confidence: 99%
“…In short, a large amount of research works have studied the human behavior while driving, using different tools to capture and extract the data (eye-tracking systems, camera with videos processing and machine learning tools, etc. ); these data were processed to extract various features such as PERCLOS (Bergasa and Nuevo 2006;Ji et al 2004;Jin et al 2013;Kong et al 2015;Friedrichs and Yang 2010;Darshana et al 2015;Sun et al 2017) and blink frequency (Bergasa and Nuevo 2006;Jin et al 2013;Friedrichs and Yang 2010;Sun et al 2017Sun et al , 2015. (More details are giving in "Driver's behavior features extraction" section).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The data output includes over 145 values covering, among others, gaze, eyelid, pupilometry and head tracking, raw and filtered gaze, blinks, fixations and saccades. Smart Eye has been used in several driver assistance and inattention systems, such as [76,143,144,145,238]. …”
Section: Sensorsmentioning
confidence: 99%
“…Numerous previous studies have shown that the duration of continuous driving without rest was signi cantly associated with the deterioration of the driving performance [9][10][11][12]. Accordingly, many researchers have focused their attention on identifying the symptoms and level of sleepiness experienced by the driver while driving, among which visual behaviour variables are the most frequently used measures [13,14]. They found that sleepy drivers exhibit certain observable visual changes, such as slow eyelid movement, small degree of eye opening (or even closed), longer blink time, frequent nodding, gaze, etc., which can be used to detect the level of sleepiness [7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%